Dobles Sentidos y Connotaciones en el Discurso Administrativo: Dispositivos de Poder en las Organizaciones (2019)
The existence of terms semmanticaly charged of diverse connotations in management discourse, has generated not only a progressive conceptual impoverishment condemning it to remain under the shadow of other disciplines well developed epistemologicaly, but also, paradoxicaly, has allowed, in management practice, the coming og solid management actions satisfaying interests unlike those intended at the beginning; those interests are: power, domination, and discipline.